Konsep Tawassul dalam Islam - Faisal Muhammad Nur (Fakultas Ushuluddin dan Filsafat UIN Ar-raniry Banda Aceh, 2011)
The concept of tawassulpracticed by number of Muslims, which is based on the quranic and Sunnah teachings, is not new in Islam. Tawassul practiced by them does not believe in others than Allah. So that, if there is a tawassulin application believes to other than Allah it is a contradiction to Qur‟an and Sunnah teachings. Tawassul practiced by muslim is different from that found in other religions such as Hindu, Budha, Shinto and others. Tawassul practiced by these religions adore their ancestors‟ spirit and believe that those spirits can fulfill all their needs.